Classification and characterization of nonequilibrium Higgs modes in unconventional superconductors - L. Schwarz (Nature Portfolio, 2020)
The lately reported Higgs modes in unconventional superconductors require a classification and characterization allowed by nontrivial symmetry of the gap and the quench pulses. Here, the authors provide a classification scheme of Higgs oscillations with their excitation processes allowing them to distinguish between different symmetries of the superconducting condensate.